Treachery in death - Robb, J. D., 1950- (New York : Berkley Books, 2011)
Investigating the senseless killing of an elderly man by three drug-addled punks, Peabody tackles the case as a new primary detective before stumbling on an operation by two corrupt fellow officers who have just committed a murder.
Originally published: New York : G.P. Putnam's Sons, 2011.
Keywords: Dallas, Eve (Fictitious character) -- Fiction; Policewomen -- New York (State) -- New York -- Fiction; Women detectives -- New York (State) -- New York -- Fiction; New York (N.Y.) -- Fiction; Romantic suspense fiction; Mystery fiction